2023
DOI: 10.3389/fgene.2022.1085785
|View full text |Cite
|
Sign up to set email alerts
|

ABI3BP is a prognosis biomarker related with clinicopathological features and immunity infiltration of lung tumor

Abstract: Background: The primary factor of cancer mortality is lung tumor. ABI3BP gene encodes an extracellular matrix bind protein associated to multiplication and derivation. However, the prognosis score of ABI3BP for lung tumor and its relation with immunity cellular infiltration for lung tumor have not been reported.Methods: Public repository systems (Timer, GEPIA, TCGA, HPA) were utilized to explore expression of ABI3BP for lung tumor, and explored the relation of ABI3BP and clinicopathological parameters. TCGA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Even if the molecular mechanisms affecting the immune response are still unknown, these data suggest that increased ABI3BP expression may impact on tumor progression also by modulating the tumor immune microenvironment. In accordance with this hypothesis, the expression of ABI3BP in lung cancer correlates with patient’s prognosis, with low expressing patients having a poorer outcome ( 28 ).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Even if the molecular mechanisms affecting the immune response are still unknown, these data suggest that increased ABI3BP expression may impact on tumor progression also by modulating the tumor immune microenvironment. In accordance with this hypothesis, the expression of ABI3BP in lung cancer correlates with patient’s prognosis, with low expressing patients having a poorer outcome ( 28 ).…”
Section: Resultsmentioning
confidence: 69%
“…ABI3BP expression has been associated with many physiological and pathological processes ( 99 ), and it is well known for its role in multiple cancer types, acting as a tumor suppressor by inhibiting cancer cell proliferation and migration and promoting cellular senescence ( 100 104 ). The role of ABI3BP in lung cancer has been investigated only recently and it has been indicated that this molecule is downregulated in the lesions compared to normal lung tissue and it gradually decreases as lung cancer progresses ( 28 ). Interestingly, in the same work, it has been demonstrated for the first time the association between ABI3BP expression and immune cell infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…ABI3BP has been reported to be associated with many immune cell marker sets in many types of cancer. Yan et al discovered that this gene set is related to biological processes such as apoptosis, cell cycle, and DNA damage and that immune infiltration of tumour cells is associated with ABI3BP expression [ 61 ]. They also found that the increased expression of ABI3BP in tumours may interfere with the tumour immune microenvironment by affecting immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the increased expression of ABI3BP in tumours may interfere with the tumour immune microenvironment by affecting immune cell infiltration. In addition, ABI3BP is involved in regulating several immune signalling molecules in lung tumours, including immunostimulants, immunosuppressants, MHC, chemokines, and receptors [ 62 ]. Wu et al [ 63 ] found a correlation between DPYSL2 expression and immune cell infiltration in lung adenocarcinomas, including macrophages, dendritic cells, CD4 + T cells, and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that extracellular matrix proteins may be important signs of aging [ 10 ]. ABI3BP, a recently discovered extracellular matrix protein, has been linked to tumor development in numerous studies [ 11 , 12 ]. Knocking down ABI3BP expression has been shown to inhibit tumor growth by affecting tumor cell proliferation, viability, migration, and invasion [ 13 ].…”
Section: Introductionmentioning
confidence: 99%